Simulation of the Impedance of the Electrical Double Layer and Evaluation of the Surface Excess Concentration by Finite Element Analysis - Alex Silva de Moraes; Evaldo Batista Carneiro Neto; Mauro Chierici Lopes (Orbital: The Electronic Journal of Chemistry, 2021)
Understanding the structure of the electrical double layer (EDL) is of great importance for many different technological and scientific applications, but some information is not always accessible from experiments. In this sense, the aim of this study was to implement a simple one-dimensional computational model for the study of the EDL and solve by the finite element method. The details of the validation of the model are presented and frequency domain analysis is performed in order to obtain impedance information. From the impedance study, it was possible to obtain the total capacitance and confirm its dependence on applied potential. Moreover, calculations of the Gibbs excess surface concentration were carried out for different values of bulk concentration. Our results are in agreement with analytical predictions, showing that the model is suitable for the study of the EDL structure.DOI: http://dx.doi.org/10.17807/orbital.v13i2.1453